Pengembangan Media Audio dan Visual Animasi Untuk Meningkatkan Pemahaman Konsep Fisika Pada Siswa Kelas XI SMAN 2 Kota Bima Tahun Ajaran 2024/2025 - Subhan, Muhammad; Kurnia Putri, Fera (Universitas Nggusuwaru, 2024)
Learning media can be defined as anything that can be used to communicate ideas and arouse students' interest and motivation while stimulating their own mental processes. The aim of this research is to develop a video-based learning media containing animations that explain physical phenomena in momentum and impulse materials using the Canva Pro application. This research is development research using the Research and Development (R&D) method and the model used is the ADDIE model (analysis, design, development, implementation and eval___uation). This product was validated by 1 media expert, 2 material experts, 3 teacher responses and 35 class XI students. In the initial stage, a validation test was carried out by media experts, material experts and teacher responses. Then test the effectiveness of the media in the form of animated audio visuals and validation tests by students. The media expert validation results obtained an average of 95.00% which is included in the Valid criteria, for the material expert and teacher validation results obtained the Very Valid category with results of 81.82% and 81.82% respectively. 97, 06%, the student validation test obtained a result of 89.6% which is included in the Very Good criteria. The results of the eval___uation of the understanding of the concept of material physics, Momentum and Impulse, with a total of 20 essay questions, if calculated, the percentage result is 76%. It can be concluded that this animated video product based on the Canva Pro application can improve understanding of physics concepts in momentum and impulse material and can also increase motivation for student learning achievement and is suitable for use in the learning process